PENGARUH SUKU BUNGA, JUMLAH PERUSAHAAN DAN PERTUMBUHAN EKONOMI TERHADAP PENYALURAN KREDIT MODAL KERJA BAGI UMKM DI SUMATERA SELATAN - Tien Yustini (University of Merdeka Malang, 2015)
To develop micro, small and middle bussiness (MSMB) depend on Working Capital Credit (WCC). WCC depends on interest rate, the amount of company and economic growth. This study aimed to analize the effect of interest rate, the amount of company and economic growth on Working Capital Credit of MSMB in South Sumatera. To process the data used instrument statistic program of Eviews 7.2 application that will give numeric output. This study used pooled data regression test with Ordinary Least Square (OLS) and using two estimation approaches: Fixed Effect model and Random Effect model. Besides, to examines the two models, it was used Hausman Test. The result showed that interest rate has positive influence to MSMB in villages/cities in South Sumatra Province with amount of interest rate 0.311346 and probability 0.0245 because the interest rate at that time was subsidized by government, so eventhough the interest rate was high people did not get trouble to borrow money in the bank. Economic growth has positive and significant influence to MSMB as amount 1.077473 because if economic growth increases so people income will increase, then the consume will increase and the output will increase too.